A phase III randomized clinical trial comparing sentinel node biopsy with no retroperitoneal node dissection in apparent early-stage endometrial cancer – ENDO-3: ANZGOG trial 1911/2020 - Obermair, Andreas; Nicklin, Jim; Gebski, Val; Hayes, Sandra C; Graves, Nicholas; Mileshkin, Linda; Lin, Ming Yin; Beale, Phillip; Baxter, Eva; Robledo, Kristy; Salomon, Carlos; Hanna, George B; et al. (International journal of gynecological cancer, 2021)
BackgroundSentinel node biopsy is a surgical technique to explore lymph nodes for surgical staging of endometrial cancer, which has replaced full retroperitoneal lymph node dissection. However, the effectiveness of sentinel node biopsy, its value to patients, and potential harms compared with no-node dissection have never been shown in a randomized trial.Primary ObjectivesStage 1 will test recovery from surgery. Stage 2 will compare disease-free survival at 4.5 years between patients randomized to sentinel node biopsy versus no retroperitoneal node dissection.Study HypothesisThe primary hypothesis for stage 1 is that treatment with sentinel node biopsy will not cause detriment to patient outcomes (lymphedema, morbidity, loss of quality of life) and will not increase treatment-related morbidity or health services costs compared with patients treated without a retroperitoneal node dissection at 12 months after surgery. The primary hypothesis for stage 2 is that disease-free survival at 4.5 years after surgery in patients without retroperitoneal node dissection is not inferior to those receiving sentinel node biopsy.Trial DesignThis phase III, open-label, two-arm, multistage, randomized non-inferiority trial (ENDO-3) will determine the value of sentinel node biopsy for surgical management of endometrial cancer. Patients with endometrial cancer are randomized to receive: (1) laparoscopic/robotic hysterectomy, bilateral salpingo-oophorectomy with sentinel node biopsy or (2) laparoscopic/robotic hysterectomy, bilateral salpingo-oophorectomy without retroperitoneal node dissection. In stage 1, 444 patients will be enrolled to demonstrate feasibility and quality of life. If this is demonstrated, we will enroll another 316 patients in stage 2.Major Inclusion and Exclusion CriteriaInclusion criteria include women aged 18 years or older with histologically confirmed endometrial cancer; clinical stage 1, who meet the criteria for laparoscopic or robotic total hysterectomy and bilateral salpingo-oophorectomy. Patients with uterine mesenchymal tumors are excluded.Primary EndpointsThe endpoint for stage 1 is surgical recovery, with the proportion of patients returning to usual daily activities at 3 months post-surgery as measured with the EQ-5D. Stage 2 is disease-free survival at 4.5 years.Sample Size760 participants (both stages).Estimated Dates for Completing Accrual and Presenting ResultsStage 1 commenced in January 2021 and is planned to be completed in December 2024 when 444 participants have completed 12 months' follow-up. Stage 2 will enroll a further 316 participants for a total of 760 patients.Trial RegistrationNCT04073706.